NILAI-NILAI PENDIDIKAN KARAKTER DALAM RITUAL TIGA BULANAN BAYI, DI DESA ADAT BANYUNING, KABUPATEN BULELENG, BALI - Suwendra, I Wayan (Jurnal Widya Sastra Pendidikan Agama Hindu, 2025)
The Tiga Bulanan Bayi ritual is unique, rare, and rich in character educational values. What character educational values are contained within it, have been scientifically researched using a qualitative research approach. The determination of informants was done through purposive snowball sampling. Data were collected through in-depth interviews, participant observation, and document recording. After the data was collected, it was analyzed using analysis techniques: categorization, domain, taxonomic, and cultural themes. From the analysis results, the values of Hindu religious education contained in the Tiga Bulanan Bayi ritual are as follows: (1). The human body (bhuana alit) and the universe (bhuana agung) must continuously be harmonized and preserved. (2) Humans should always be grateful for God's grace because they have been granted the universe and its contents as a means of life for all living beings. (3) Hindus are required to study philosophy, ethics, and Hindu religious rituals because the egg duel is used as the core of the Tiga Bulanan Bayi ritual. The deepest meaning of this ritual is the contest of philosophy/tattwa, the contest of ethics/Susila related to morality, and the contest of rituals thatlead to ethics and philosophy. It is recommended that the Tiga Bulanan Bayi ritual be continuously preserved.